The Impact of Low-Skill Refugees on Youth Education - Semih Tumen (Institute of Labor Economics (IZA), 2018)
This paper examines the impact of Syrian refugees on high school enrollment rates of native youth in Turkey. Syrian refugees are, on average, less skilled and more willing to work in low-pay informal jobs than Turkish natives. Refugees can influence native youth's school enrollment likelihood negatively through educational experience. But, at the same time, they can affect enrollment rates positively as they escalate competition for jobs with low-skill requirements. Using micro data from 2006 to 2016 and employing quasi-experimental methods, I find that high-school enrollment rates increased 2.7-3.6 percentage points among native youth in refugee-receiving regions. Furthermore, a one-percentage point increase in the refugee-to-population ratio in a region generates around 0.4 percentage point increase in native's high school enrollment rates. Most of the increase in high school enrollment comes from young males with lower parental backgrounds, which is consistent with the hypothesis that the main mechanism operates through the low-skill labor market. The regressions control for (i) variables proxying parental investment in human capital such as parental education, being in an intact family, and household size, (ii) regional economic activity, and (iii) regional availability of high schools and high school teachers.
Keywords: I25; J61; 330; low-skill Syrian refugees; youth education; high school enrollment